The Phenomenon of Bai’ An-Najasy Practices in E-Commerce from a Sharia Economics Perspective - Safitri, Denta; Erdiansah, Alim; Darma Yanti, Juli; Rozalinda (Jurnal Iqtisaduna, 2024)
This research was conducted with the aim of analyzing the phenomenon of bai’ an-najasy on e-commere , namely comments that praise goods, even though they are not appropriate at the time of receipt of goods, this is done to increase sales. This type of research is qualitative, namely research based on descriptions of words and sentences that are carefully and methodically arranged, from data collection to interpretation and reporting of research findings. data collection using field research methods with interviews and participatory observation, where researchers are involved in the daily activities of the people observed. Thetype of data is primary data with data sources, namely information collected directly from the field, namely consumers who have made purchase transactions on e-commerce in Kerinci Regency and actively participate in buying and selling on e-commerce. The sample was determined using the snowball sampling method, the data was analyzed descriptively. The results showed that33 out of 40 consumers felt market engineering and although 7 people did not feel the same way, the problem of the phenomenon of bai’ an-najasy practice still often occurs among e-commerce users in the community in Kerinci Regency.